Comparison of Efficacy of Latanoprost 0.005% with Bimatoprost 0.01% in Patients with Open Angle Glaucoma (Medical Forum Monthly, 2024)
Objective: To compare the mean change in intraocular pressure with Latanoprost 0.005% and Bimatoprost 0.01% in patients with open angle glaucomaStudy Design: Randomized open clinical trial.Place and Duration of Study: This study was conducted at the outpatient department of Ophthalmology, Bahawal Victoria Hospital, Bahawalpur from December, 2015 to November 2016. Materials and Methods: 60 diagnosed patients of open angle glaucoma age group 20 to 50 years were included coming to eye OPD having intraocular pressure greater than 20 millimeter of mercury at 8:00am. The patients were allotted group A or group B by the lottery method. The group A was considered as Latanoprost group while group B as Bimatoprost group. Group A was treated with Latanoprost 0.005% while the group B with Bimatoprost 0.01% as mono-therapy with one drop daily in conjunctival sac as topical administration at 05.00 p.m for 29 days, beginning on day 0 of the study. Follow up visits were conducted on day 30 at 8 am and IOP of both eyes were measured and mean reduction in IOP was noted.Results: Difference between base line and day 30 IOP right eye of male patients in group A was 6.75+/- 0.52mmHg while in group B was 7.58 +/- 0.24mmHg (P=0.001) and the difference between base line and day 30 IOP Left eye of male patients in group A was 6.60 +/-0.70mmHg while in group B was 7.28 +/- 0.38mmHg. (P=0.0031)The difference between base line and day 30 IOP right eye of female patients in group A was 6.18 +/- 0.01mmHg while in group B was 7.06 +/- 0.06mmHag (P=0.0001) & difference between base line and day 30 IOP Left eye of female patients in group A was 6.36 +/- 0.10 mmHg while in group B was observed 8.0 +/- 0.31mmHg. (P=0.001)Conclusion: Current study showed that mean change in reducing the intraouclar pressure with Bimatoprost 0.001% is more significant than Latanprost 0.005